Fluvial remote sensing for science and management - Carbonneau, Patrice (Advancing river restoration and management., 2012)
This book offers a comprehensive overview of progress in the general area of fluvial remote sensing with a specific focus on its potential contribution to river management. The book highlights a range of challenging issues by considering a range of spatial and temporal scales with perspectives from a variety of disciplines. The book starts with an overview of the technical progress leading to new management applications for a range of field contexts and spatial scales. Topics include colour imagery, multi-spectral and hyper-spectral imagery, video, photogrammetry and LiDAR. The book then discusses management applications such as targeted, network scale, planning, land-use change modelling at catchment scales, characterisation of channel reaches (riparian vegetation, geomorphic features) in both spatial and temporal dimensions, fish habitat assessment, flow measurement, monitoring river restoration and maintenance and, the appraisal of human perceptions of riverscapes. Key Features: * A specific focus on management applications in a period of increasing demands on managers to characterize river features and their evolution at different spatial scales * An integration across all scales of imagery with a clear discussion of both ground based and airborne images * Includes a wide-range of environmental problems * Coverage of cutting-edge technology * Contributions from leading researchers in the field